Mukti Ali’s Contributions to Interreligious Harmony in Indonesia - Toguan Rambe (al-Lubb: Journal of Islamic Thought and Muslim Culture, 2020)
This study explores Mukti Ali’s thoughts and contributions to Inter-religious harmony. Thoughts by Mukti Ali were discussed the harmony among religious believers, including comparative religion, the concept of agreeing in disagreement, and inter-religious dialogue, all anchored to the doctrine of Islam rahmat li al-’alamin. Mukti Ali pioneered interfaith dialogue as well-known moderate, dialogue, and respect for pluralism, improving justice and peace, understanding each other, and respecting each other within the frame of national unity. Throughout his life, Mukti Ali was known as a staunch Islamic thinker to fight for inter-religious harmony in Indonesia. The whole struggle and contribution in interreligious harmony at least touch some aspects; those are the scientific aspects and social relations. His persistence has a strong theological foundation. Her eagerness Mukti Ali was also known as the father of national harmony in Indonesia.